Distorções no leilão de fechamento de ações da BMF&BOVESPA - Vieira, Carlos Jourdan Gadelha (2011)
The closing price of a stock is the most important reference for the fair value of the company. Given its broad use in several contracts and in situations of asymmetrical information, brokers, traders and fund managers alike have incentives to manipulate it. This essay studies the intraday records of all transactions in the BMF&BOVESPA stock exchange between april 4th 2006 and march 31st 2011, and finds evidence of distortions in both volume and volatility at the end of the day, as well as price reversals in the next morning. It is also shown that the magnitude of the distortions are in line with such incentives.